2017
DOI: 10.1016/j.jinf.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Real-world persistence with antiretroviral therapy for HIV in the United Kingdom: A multicentre retrospective cohort study

Abstract: SummaryObjectivesPersistence with an antiretroviral therapy (ART) regimen for HIV can be defined as the length of time a patient remains on therapy before stopping or switching. We aimed to describe ART persistence in treatment naïve patients starting therapy in the United Kingdom, and to describe differential persistence by treatment regimen.MethodsWe performed a retrospective cohort study at eight UK centres of ART-naïve adults commencing ART between 2012 and 2015. Aggregate data were extracted from local tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 11 publications
7
17
0
Order By: Relevance
“…Although outside the scope of the current analysis, future research should investigate reasons for discontinuation and switching of therapy. Past research has reported that factors including pill burden, poor tolerability, risk of resistance due to complexity, toxicity, regimen performance, drug efficacy, and virologic failure could be possible reasons for higher rates of discontinuation among MTR patients [20,37,40]. Furthermore, the current study also showed that among STRs, patients who were treated with EVG/COBI/FTC/TAF had greater persistence compared to those treated with other STRs.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Although outside the scope of the current analysis, future research should investigate reasons for discontinuation and switching of therapy. Past research has reported that factors including pill burden, poor tolerability, risk of resistance due to complexity, toxicity, regimen performance, drug efficacy, and virologic failure could be possible reasons for higher rates of discontinuation among MTR patients [20,37,40]. Furthermore, the current study also showed that among STRs, patients who were treated with EVG/COBI/FTC/TAF had greater persistence compared to those treated with other STRs.…”
Section: Discussionsupporting
confidence: 52%
“…Amongst third agents, INSTIs are the most preferred as evident in studies that showed it be superior or equivalent to other third agents in safety and efficiency. In addition, it is reported that INSTIs are more tolerable to patients, in turn reducing discontinuation rates [20][21][22][23]. However, for patients that are at higher risk of non-adherence, PIs as the third agent would be most appropriate because of their genetic barrier to resistance [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analyses of durability have compared people receiving the two NNRTIs without accounting, in the study entry criteria, for the fact that RPV use is restricted to people with an untreated HIV RNA level < 100 000 copies/mL. This makes the interpretation of the comparisons even more difficult [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective cohort study at eight UK centers, Lewis et. al. found that the rilpivirine based STR (complera) had a significantly lower discontinuation rate than another STR (atripa) and other third agents [5]. In another study from Maple Leaf Medical Clinic in Canada, researchers found that being on an integrase strand transfer inhibitor (INSTI) or nonnucleoside reverse transcriptase inhibitor (NNRTI)-based regimens versus protease inhibitors (PI) regimen were associated with better durability.…”
Section: Introductionmentioning
confidence: 99%